Biomimetic hydrogel scaffolds for stimulating fibrotic responses: development of an in-vitro assay for implant material testing - Spoddig, VJ; Murkar, Rasika S.; Kopp, Sascha; Walles, Heike (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe foreign body response (FBR) is a complex immune response that affects implant integration and function. Conventional in vivo models are limited by ethical and reproducibility issues, emphasising the necessity for reliable in vitro alternatives. The objective of this study was to develop a standardised in vitro test using a collagen hydrogel-based 3D co-culture system to simulate FBR.MethodologyA 3D hydrogel model was co-cultured with human fibroblasts and macrophages to investigate immune responses to implant materials such as ceramic, titanium and steel. Cytokine expression and ECM remodelling were measured over a 14-day period to characterise material-specific responses.ResultsThe hydrogel model enabled a detailed analysis of the immune response to different materials. The material with the strongest fibrotic response was titanium, which resulted in a notable increase in collagen and TGF-β1 in M2 macrophage cultures. Furthermore, the emergence of IL-6 and IL-4 as prominent cytokine trends provided valuable insight into the inflammatory and regenerative response.DiscussionThe model demonstrates that titanium exhibits a probable propensity for fibrosis, a finding that is corroborated by elevated TGF-β1 levels. IL-6 has been identified as a significant marker for inflammatory reactions. The results offer new perspectives for the development of patient-specific models, and future studies should include the comparison of fibroblasts from patients who have responded to implants with those who have not.ConclusionThe 3D hydrogel model offers a promising, cost-effective in vitro alternative for studying FBR and allows for a more accurate analysis of immune responses to implants. Future studies should further investigate the interactions of fibroblasts and macrophages and compare the immune responses between different patient groups to better understand the mechanisms behind different responses.